2012
DOI: 10.1159/000178518
|View full text |Cite
|
Sign up to set email alerts
|

Kruppel-like Factor-15 Inhibits the Proliferation of Mesangial Cells

Abstract: Background/Aims: The Kruppel-like factor-15 (KLF15), a DNA-binding transcription factor, is highly expressed in endothelial and mesangial cells of the kidney. However, its effects on mesangial cell proliferation have not previously been investigated. In this study, we investigated the effect of KLF15 on mesangial cell proliferation. Methods: We established a classic rat anti-Thy1 mesangial proliferative nephritis model. Affymetrix rat U230 2.0 chip was used to detect the gene expression profiles at different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Besides, Konishi J et al showed that inhibition of Notch signaling by a γ-secretase inhibitor suppresses the growth of non-small cell lung cancer (NSCLC) [41]. Accumulating evidence suggests that Notch signaling plays a critical role in the development of several types of cancer, functioning as a tumor promoter [4452]. NOTCH1 has been shown to be a gene that promotes cell proliferation [53, 54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, Konishi J et al showed that inhibition of Notch signaling by a γ-secretase inhibitor suppresses the growth of non-small cell lung cancer (NSCLC) [41]. Accumulating evidence suggests that Notch signaling plays a critical role in the development of several types of cancer, functioning as a tumor promoter [4452]. NOTCH1 has been shown to be a gene that promotes cell proliferation [53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…In the human breast cancer-derived cell line T47D, KLF15 has been reported to decrease estrogen-dependent cell proliferation [43]. KLF15 inhibits the proliferation of mesangial cells [44]. Besides, KLF15 suppresses cell proliferation of mesangial cells under high glucose [45] and it negatively regulates estrogen-induced epithelial cell proliferation by inhibition of DNA replication [43].…”
Section: Discussionmentioning
confidence: 99%
“…KLF15 is a key regulator of podocyte differentiation, and a loss of KLF15 increases the susceptibility to kidney injury ( 25 ). KLF15 is highly expressed in the normal endothelial and mesangial cells of the kidney ( 26 ). NF-κB is a downstream target gene of KLF15, and KLF15 affects the downstream cascade reaction by regulating the expression of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…KLF6 expression was induced in cultured glomerular mesangial cells in the setting of sublytic complement-mediated apoptosis (55). In addition, KLF15 expression was reduced in mesangial cells during the proliferative phase of Thy-1 rat model of mesangial glomerulonephritis (21). Interestingly, modulating the expression of KLF15 in cultured mesangial cells inversely regulated the levels of E2F1, cyclin D1, and CDK2 expression.…”
Section: Klfs In Glomerular Diseasementioning
confidence: 99%